From Pulpit to Sidewalk: Reverend Agus Sutikno’s Social and Symbolic Practices in Forming an Emancipatory Community for Vagrant Kids: Dari Mimbar ke Trotoar: Praktik Sosial dan Simbolik Pendeta Agus Sutikno dalam Membentuk Komunitas Emanspiatoris Bagi Anak Jalanan - Kinasih, Maria Dominika Tyas; Birsyada, Muhammad Iqbal (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
Street children are part of marginalized communities. The presence of street children often causes stigma, such as: synonymous with violence, juvenile delinquency, and moral degradation. However, there are communities that accept, embrace, and care for street children. One of them, comes from a religious figure, namely Pastor Agus Sutikno. The figure, who has a unique and eccentric appearance, dedicates his life to caring for street children. This type of research is an interpretative Phenomenological Research with a qualitative approach. Data collection was done with data collection tools used in this study in the form of observation, documentation, in-depth interviews, and literature studies. The results of research showed that the ministry conducted by Pastor Agus Sutikno does not look at ethnicity, religion, race, and Customs and through this ministry, street children get education and work.